Chronic viral infections impinge on naive bystander CD8 T cells. Issue 3 (26th March 2020) - Barnstorf, Isabel; Welten, Suzanne P. M.; Borsa, Mariana; Baumann, Nicolas S.; Pallmer, Katharina; Joller, Nicole; Spörri, Roman; Oxenius, Annette
Abstract: Introduction: Epidemiological data suggest that persistent viral infections impair immune homeostasis and immune responsiveness. Previous studies showed that chronic virus infections negatively impact bystander T‐cell differentiation and memory formation but there is limited knowledge of how chronic virus infections impinge on heterologous naive T‐cell populations. Methods: We used adoptive transfer of naive CD8 T cells with defined nonviral specificity into hosts, which were subsequently chronically infected with lymphocytic choriomeningitis virus, followed by analyses of numeric, phenotypic, and functional changes provoked in the chronically infected host. Results: We demonstrate that chronic virus infections have a profound effect on the number and phenotype of naive bystander CD8 T cells. Moreover, primary expansion upon antigen encounter was severely compromised in chronically infected hosts. However, when naive bystander CD8 T cells were transferred from the chronically infected mice into naive hosts, they regained their expansion potential. Conversely, when chronically infected hosts were supplied with additional antigen‐presenting cells (APCs), primary expansion of the naive CD8 T cells was restored to levels of the uninfected hosts. Conclusions: Our results document numeric, phenotypic, and functional adaptation of bystander naive CD8 T cells during nonrelated chronic viral infection. Their functional impairment was only evident in the chronically infected host, indicating that T‐cell extrinsic factors, in particular the quality of priming APCs, are responsible for the impaired function of naive bystander T cells in the chronically infected hosts. Abstract : We investigated how chronic virus infections impinge on heterologous naive T‐cell populations, using adoptive transfers of naive CD8 T cells with defined nonviral specificity. Naive bystander CD8 T cells were numerically reduced, phenotypically altered, and their primary expansion upon antigenic rechallenge was severely compromised in chronically infected hosts. However, the impaired expansion potential was only evident in the chronically infected host, indicating that T‐cell extrinsic factors are responsible for this impairment.